A spatial-economic optimisation of waste to biomethane in Malaysia - Hoo, Poh Ying (2019)
With ever growing population and demand for energy worldwide, the world is facing one of the most prominent issues of the century, environmental sustainability. The resources of the earth are nonetheless finite, the question is how can the limited resources be consumed in a more sustainable way? In the last decades, it has been observed that the energy sector is experiencing transition from fossil fuels to renewable sources, among which included biogas. Biogas is a type of bioenergy produced when organic matters are digested anaerobically. International Energy Agency (IEA) recently highlighted the diversity of benefits of biogas and anaerobic digester (AD) in the advent of circular economy in one of its report last year in 2018. The uniqueness of biogas as compared to other types of bioenergy lies in its production not only coming from energy crops, but also organic wastes. Despite being world second biggest palm oil producer, biogas (produced from palm oil mill effluent, POME) and AD are limitedly covered for its huge potential in Malaysia. Not to mention also the abundant availability of organic waste which could act as feedstock for AD. With raising concern on environmental pollution caused by the oil palm industry, biogas and AD could serve as an opportunity to reflect and showcase on sustainable planting of palm oil by taking massive adoption, but not merely a tag along option with renewable energy transition or waste management, as reflected in the current policy. Malaysian government has implemented Feed-in tariff mechanism since 2011 to promote the industry to adopt renewable energy (RE), which included biogas. However, lack of systematic planning of biogas supply chain, economic competitiveness of biogas and availability of infrastructure have become hindrance to harvest the benefits of biogas optimally. Thus, this study aims to explore potential of biogas upgrading to biomethane and the techno-economic feasibility of biomethane injection into the natural gas grid. An operational optimisation model, biomethane injection operational (BIOP) model was developed to study the relation between biomethane pressure, consumer demand and supply distance. It has found that in a supply distance of less than 50 km, most biomethane is supplied to industrial consumers despite having higher pressure requirement (20 psig), at the annual cost of 1.85 times higher than Business as Usual (BaU), due to high demand by industrial consumers. The study is then followed by an economic assessment to identify feasible FiT range for biomethane production from different feedstock, namely POME, food waste, cattle manure and chicken manure. The proposed FiT range, 59.79 – 147.82 MYR/GJ is economically incompetent for biomethane to compete in the energy market, unless there is government development plan to build distribution and injection infrastructure, which could bring down the cost significantly. Lastly, BeWhere ©, a spatial-techno-economic optimisation model was then adopted and extended to tackle the limitation of biogas utilisation due to location constraints. Optimised result shows that on-site biomethane plant using food waste as feedstock is the preferred configuration. Besides taking into account the environmental cost through carbon price (500 MYR/tCO2), it has found that simultaneous rationalisation of natural gas subsidy (25 – 130 MYR/GJ) and attractive incentive for biomethane production (38 – 190 MYR/GJ) is required to make biomethane market competitive.